2003
DOI: 10.1182/blood-2002-11-3396
|View full text |Cite
|
Sign up to set email alerts
|

Serine phosphorylation of STAT3 is essential for Mcl-1 expression and macrophage survival

Abstract: The Bcl-2 family member Mcl-1 is essential for macrophage survival. However, the mechanisms that contribute to the expression of Mcl-1 in these cells have not been fully characterized. The present study focused on the role of signal transducer and activator of transcription 3 (STAT3) in regulation of Mcl-1 in macrophages. Sodium salicylate (NaSal) treatment induced apoptotic cell death in primary human macrophages in a dose-and time-dependent fashion. Incubation with NaSal resulted in the loss of mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 66 publications
(108 reference statements)
9
113
1
Order By: Relevance
“…For example, the high level of Bcl XL expressed in the Fas-resistant myeloma cell line U266 is reduced upon STAT3 inactivation, whereupon the cells undergo apoptosis (Catlett-Falcone et al, 1999). More recently, STAT3 has been implicated in the expression of Mcl-1, another Bcl-2 prosurvival family member, and members of the inhibitors of apoptosis (IAP) family in human macrophages and neutrophils, respectively (Hasegawa et al, 2003;Liu et al, 2003). While loss of Mcl-1 is associated with cytochrome c release from mitochondria and the activation of procaspase 9, IAPs are reported to interfere with the activation of procaspases 8 and 9 (Deveraux et al, 1998).…”
Section: Role Of Stat3 In Bc Cell Proliferationmentioning
confidence: 99%
“…For example, the high level of Bcl XL expressed in the Fas-resistant myeloma cell line U266 is reduced upon STAT3 inactivation, whereupon the cells undergo apoptosis (Catlett-Falcone et al, 1999). More recently, STAT3 has been implicated in the expression of Mcl-1, another Bcl-2 prosurvival family member, and members of the inhibitors of apoptosis (IAP) family in human macrophages and neutrophils, respectively (Hasegawa et al, 2003;Liu et al, 2003). While loss of Mcl-1 is associated with cytochrome c release from mitochondria and the activation of procaspase 9, IAPs are reported to interfere with the activation of procaspases 8 and 9 (Deveraux et al, 1998).…”
Section: Role Of Stat3 In Bc Cell Proliferationmentioning
confidence: 99%
“…The primary human macrophages used in this study were differentiated in vitro for 7 days from monocytes, which were purified by elutriation from the PB of healthy donors, as previously described (32)(33)(34)(35)(36)(37). Purified monocytes were suspended in medium without fetal bovine serum (FBS) and allowed to adhere to cell culture dishes for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Purified monocytes were suspended in medium without fetal bovine serum (FBS) and allowed to adhere to cell culture dishes for 1 hour. Afterward, medium was changed to RPMI 1640 supplemented with 20% FBS, 100 units penicillin, 100 g/ml streptomycin, and 1 g/ml polymyxin B. Adherent cells were allowed to differentiate into normal control macrophages, as previously described (32)(33)(34)(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that serine phosphorylation of STAT3 modulates its maximum activity, perhaps by affecting the recruitment of co-factors (14,40), whereas Tyr 705 phosphorylation is required for the activation. However, recent studies have suggested that STAT3 can be activated through Ser 727 phosphorylation in the absence of Tyr 705 phosphoryla- tion, involving, for instance, Notch signaling in neuronal stem cells (41) or constitutive activation of STAT3 in macrophages (42). Most recently, Ser 727 -phosphorylated and Tyr 705 -dephosphorylated STAT3 is shown to promote prostate tumorigenesis (43).…”
Section: Discussionmentioning
confidence: 99%